Corrosion-resistant polyion liquid coating and preparation method thereof
By coating polyionic liquid on Cu@Cu(OH)2 filter material, the problem of poor chemical stability of copper hydroxide is solved, and the oil-water separation performance and the separation ability are improved in harsh environments.
Patent Information
- Application Number
- CN202411454418.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The poor chemical stability of copper hydroxide in the prior art limits its widespread use in the field of oil-water separation.
Cu@Cu(OH)2 was prepared by copper mesh, and Cu@Cu(OH)2-PIL filter material was prepared by using polyionic liquid (PIL) as a protective coating. The method includes cleaning and processing of the copper mesh, synthesizing 3-ethyl-1-vinylimidazole bromine salt and polyionic liquid, and finally coating Cu@Cu(OH)2 with PIL.
It improves the structural and chemical stability of Cu@Cu(OH)2 in harsh environments, maintains good oil-water separation performance, and even has a certain separation ability in acidic environments.
Smart Images

Figure CN119425227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid coatings, in particular to a corrosion-resistant polyionic liquid coating and a preparation method thereof. Background Art
[0002] With the rapid development of industry, frequent oil spills and the random discharge of wastewater and oil / organic solvents have had an adverse impact on the global environment and ecosystem. On the other hand, the presence of water in engine oil can also cause the oil to have effects such as reduced lubrication performance, increased oxidation and corrosion, and emulsification, thereby reducing the efficiency and life of the engine. Therefore, efficient oil-water separation technology has attracted much attention. Traditional methods (such as combustion, mechanical collection, and chemical dispersion) have been used to remove oil and organic solvents from water, but they are inefficient and prone to secondary pollution. Materials with special wettability are considered to be important candidates for efficient oil-water separation due to their different affinities for water and oil.
[0003] Metal meshes, such as copper and stainless steel, have been widely studied as substrates for oil-water separation membranes because of their porous structure, superior mechanical properties, low cost, feasibility of large-scale production, and ease of adjusting their microstructure and chemical composition. Among them, copper mesh, as a common metal filter, has excellent stability, flexibility, and corrosion resistance. In addition, rough microstructures such as nanorods, nanoneedles, and nanowires can be easily prepared on copper mesh by simple methods. Among these rough microstructures, copper hydroxide nanostructures constructed on the surface of copper mesh show excellent performance in terms of special wettability due to the hydrophilic functional groups on its surface. For example, Huaiyuan Wang et al. prepared superhydrophilic and underwater superoleophobic Cu(OH) 2 The nanoneedle-coated copper mesh achieved an oil / water separation efficiency of more than 99.5%. HaoLi et al. formed four different surface morphologies of Cu(OH)2+, namely, needle-shaped, bamboo-leaf-shaped, pine-needle-shaped and peony-shaped, on the surface of the Cu mesh by controlling the oxidation time and temperature of the chemical reaction. 2 or CuO, the superhydrophilicity and superoleophilicity of these materials make them have excellent oil / water separation efficiency. 2 The chemical stability of Cu(OH) is poor, which affects its structural stability and separation effect when performing oil-water separation in harsh environments such as industrial wastewater. 2 A protective coating is added to the surface to prevent the external environment from contacting Cu(OH) 2 Direct contact and chemical reaction are the main factors to increase Cu(OH) 2 An effective method for structural stability.
[0004] Poly(ionic liquid) (PIL) is a polymer composed of a repeating unit ionic liquid (IL) and a polymer backbone. They are highly chemically inert, not easily corroded or decomposed by chemicals, and can exist stably with many chemicals. Polyionic liquids have shown great potential as protective coatings in many fields. For example, Shimou Chen et al. proposed a multifunctional water-blocking polyzwitterionic liquid coating, poly([2-(methacryloxy)ethyl]dimethyl-(3-sulfopropyl)-tert-butyl acrylate), as a protective layer for zinc metal anodes to prevent water molecules from contacting the zinc metal anode, thereby inhibiting hydrogen evolution reactions and electrode corrosion. Douglas L. Gin et al. studied a curable imidazole poly(ionic liquid) / ionic liquid coating that can remove up to >99% of the o-dichlorobenzene liquid coated on the substrate by adsorption, and can be used for sealing and decontamination of surfaces in contact with toxic industrial chemicals. Using polyionic liquids as Cu(OH) 2 When the protective coating is applied, the easily damaged Cu(OH) 2 Wrapped in polyionic liquid film, it prevents Cu(OH) 2 The layer suffers structural damage or chemical reaction, which improves the structural and chemical stability of the copper hydroxide mesh in the oil-water separation process. In addition, the hydrophilic / hydrophobic properties of polyionic liquids are flexible and easy to control. By selecting suitable ionic liquid monomers for polymerization, the coating can show a specific affinity for oil and water, enhancing the separation ability of the copper hydroxide mesh for oil-water mixtures.
[0005] However, the poor chemical stability of copper hydroxide under the existing technology limits its widespread use in the field of oil-water separation.
[0006] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a polyionic liquid coating with corrosion resistance and a preparation method thereof, so as to solve the technical problems raised in the background technology.
[0008] To achieve the above object, the present invention provides the following technical solution, a method for preparing a corrosion-resistant polyionic liquid coating, comprising at least the following steps:
[0009] S1: After cleaning the copper mesh, it is treated with HCl solution and then soaked in HCl solution, and then further soaked in a mixed alkaline solution to complete Cu@Cu(OH) 2 Preparation of
[0010] S2: preparing a polyionic liquid, wherein the preparation of the polyionic liquid includes synthesizing 3-ethyl-1-vinyl imidazolium bromide and preparing a PIL;
[0011] S3: Cu@Cu(OH) based on S1 and S2 2 - Preparation of PILs.
[0012] Furthermore, the S1 at least comprises the following steps:
[0013] Cut a 180-220 mesh copper mesh into a square with a size of 1-3 cm*1-3 cm, and ultrasonically clean it in anhydrous ethanol and water for 8 min to 16 min respectively;
[0014] Soak the cleaned copper mesh in 6 mL to 18 mL of HCl for 8 min to 16 min to remove organic pollutants and the oxide layer;
[0015] The copper mesh soaked in hydrochloric acid was then washed with a large amount of water for 3 to 5 times, and the washed copper mesh was immersed in a solution containing NaOH (2 to 3 mol / L) and (NH 4 ) 2 S 2 O 8 (0.1~0.2mol / L) in 40mL~80mL mixed alkaline solution for 5min~15min, then wash with distilled water;
[0016] Then, it was placed on a watch glass and dried under vacuum conditions at 45°C to 65°C for 1.5h to 3h to obtain Cu@Cu(OH) 2 .
[0017] Further, the synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 at least comprises the following steps:
[0018] The synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 at least comprises the following steps:
[0019] Weigh 4.5 g to 5.0 g of 1-vinylimidazole and 5.0 g to 6.0 g of ethyl bromide in a flask, and stir at a certain temperature for 48 h to 96 h, wherein the temperature includes 15 ° C to 25 ° C;
[0020] The synthesized 3-ethyl-1-vinylimidazolium bromide is washed with ethyl acetate and ether for multiple times, and then dried in vacuum at room temperature for 8h to 14h to obtain 3-ethyl-1-vinylimidazolium bromide, which is IL-Br.
[0021] Furthermore, the preparation of the PIL in S2 at least comprises the following steps:
[0022] Dissolve 3-ethyl-1-vinyl imidazolium bromide monomer and azobisisobutyronitrile as a free radical initiator in twice the weight of methanol at a ratio of 49 to 52:1, store under nitrogen atmosphere, and react at 55°C to 70°C for 4h to 8h;
[0023] The prepared PIL is washed with methanol to remove unreacted monomers, then extracted with cold acetone and centrifuged, and finally dried in a vacuum drying oven at 50° C. to 60° C. for 7 h to 8 h to obtain the prepared PIL, which is a polyionic liquid.
[0024] Furthermore, the S3 at least includes the following steps:
[0025] Weigh PIL and methanol in a mass ratio of 1:2, dissolve PIL, and then prepare Cu@Cu(OH) 2 Soak in PIL methanol solution for 20 to 30 minutes;
[0026] Then, it was immersed in methanol for 0.5 h to 1 h to wash away the excess polyionic liquid on the surface, and finally vacuum dried at 50 ° C to 70 ° C for 2 h to 3 h to obtain Cu@Cu(OH) 2 -PIL.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention adopts the ionic liquid monomer 3-ethyl-1-vinyl imidazolium bromide to prepare a polyionic liquid (PIL) by free radical polymerization, and then coats the PIL on a super-hydrophilic Cu(OH) 2 Cu@Cu(OH) nanoneedles coated with copper mesh 2 On the filter material, polyionic liquid is used as Cu(OH) 2 Protective coating, prepared Cu@Cu(OH) 2 -PIL filter material not only has the ability to separate oil and water in wastewater environment, but also has a certain ability to separate organic solvents with different polarities. XRD, SEM, XPS and other methods were used to analyze Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL, and Cu@Cu(OH) after immersion in acid, alkali, and salt solutions 2 and Cu@Cu(OH) 2 -PIL analysis showed that Cu@Cu(OH) 2 The copper hydroxide layer on the surface collapsed seriously; after HCl immersion, the surface Cu(OH) 2 It completely reacts with HCl and loses its separation ability. However, the PIL-coated Cu@Cu(OH) 2-PIL still retains a complete nano-copper hydroxide layer after being soaked in NaOH and NaCl, and retains some Cu(OH) after being soaked in HCl 2 Therefore, the filter material still maintains good oil-water separation performance in harsh environments such as acid, alkali, and salt, showing good chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 is the NMR image of 3-ethyl-1-vinylimidazolium bromide of the present invention;
[0031] Figure 2 The infrared spectra of the 3-ethyl-1-vinylimidazolium bromide (IL-Br) monomer and PIL of the present invention;
[0032] Figure 3 is the XRD pattern of the filter material of the present invention;
[0033] Figure 4 is a SEM image of the filter material of the present invention, wherein Figure 4 (a) is the original copper mesh; Figure 4 (b) Cu@Cu(OH) 2 ; Figure 4 (c) Cu@Cu(OH) 2 -PIL; Figure 4 (d) Cu@Cu(OH) 2 [HCl]; Figure 4 (e) Cu@Cu(OH) 2 [NaOH]; Figure 4 (f) is Cu@Cu(OH) 2 [NaCl]; Figure 4 (g) is Cu@Cu(OH) 2 -PIL[HCl]; Figure 4 (h) is Cu@Cu(OH) 2 -PIL[NaOH]; Figure 4 (i) Cu@Cu(OH) 2 -PIL[NaCl].
[0034] Figure 5 It is the XPS graph of the filter material of the present invention;
[0035] Figure 6This is a picture of the surface water contact angle of the filter material of the present invention. Figure 6 (a) is the original copper mesh; Figure 6 (b) Cu@Cu(OH) 2 ; Figure (c) is Cu@Cu(OH) 2 -PIL);
[0036] Figure 7 Graph showing separation efficiency and separation flux of the filter material of the present invention;
[0037] Figure 8 It is a diagram of the separation efficiency and separation flux of the filter material under severe conditions of the present invention. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0039] Embodiment 1:
[0040] A method for preparing a corrosion-resistant polyionic liquid coating comprises at least the following steps:
[0041] S1: After cleaning the copper mesh, it is treated with HCl solution and then soaked in HCl solution, and then further soaked in a mixed alkaline solution to complete Cu@Cu(OH) 2 Preparation of
[0042] S2: preparing a polyionic liquid, wherein the preparation of the polyionic liquid includes synthesizing 3-ethyl-1-vinyl imidazolium bromide and preparing a PIL;
[0043] S3: Cu@Cu(OH) based on S1 and S2 2 - Preparation of PILs.
[0044] Furthermore, the S1 at least comprises the following steps:
[0045] Cut a 180-220 mesh copper mesh into a square with a size of 1-3 cm*1-3 cm, and ultrasonically clean it in anhydrous ethanol and water for 8 min to 16 min respectively;
[0046] Soak the cleaned copper mesh in 6 mL to 18 mL of HCl for 8 min to 16 min to remove organic pollutants and the oxide layer;
[0047] The copper mesh soaked in hydrochloric acid was then washed with a large amount of water for 3 to 5 times, and the washed copper mesh was immersed in a solution containing NaOH (2 to 3 mol / L) and (NH 4 )2 S 2 O 8 (0.1~0.2mol / L) in 40mL~80mL mixed alkaline solution for 5min~15min, then wash with distilled water;
[0048] Then, it was placed on a watch glass and dried under vacuum conditions at 45°C to 65°C for 1.5h to 3h to obtain Cu@Cu(OH) 2 .
[0049] Further, the synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 at least comprises the following steps:
[0050] The synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 at least comprises the following steps:
[0051] Weigh 4.5 g to 5.0 g of 1-vinylimidazole and 5.0 g to 6.0 g of ethyl bromide in a flask, and stir at a certain temperature for 48 h to 96 h, wherein the temperature includes 15 ° C to 25 ° C;
[0052] The synthesized 3-ethyl-1-vinylimidazolium bromide is washed with ethyl acetate and ether for multiple times, and then dried in vacuum at room temperature for 8h to 14h to obtain 3-ethyl-1-vinylimidazolium bromide, which is IL-Br.
[0053] Furthermore, the preparation of the PIL in S2 at least comprises the following steps:
[0054] Dissolve 3-ethyl-1-vinyl imidazolium bromide monomer and azobisisobutyronitrile as a free radical initiator in twice the weight of methanol at a ratio of 49 to 52:1, store under nitrogen atmosphere, and react at 55°C to 70°C for 4h to 8h;
[0055] The prepared PIL is washed with methanol to remove unreacted monomers, then extracted with cold acetone and centrifuged, and finally dried in a vacuum drying oven at 50° C. to 60° C. for 7 h to 8 h to obtain the prepared PIL, which is a polyionic liquid.
[0056] Furthermore, the S3 at least includes the following steps:
[0057] Weigh PIL and methanol in a mass ratio of 1:2, dissolve PIL, and then prepare Cu@Cu(OH) 2 Soak in PIL methanol solution for 20 to 30 minutes;
[0058] Then, it was immersed in methanol for 0.5 h to 1 h to wash away the excess polyionic liquid on the surface, and finally vacuum dried at 50 ° C to 70 ° C for 2 h to 3 h to obtain Cu@Cu(OH) 2 -PIL.
[0059] Embodiment 2:
[0060] Based on the above embodiment 1, a preferred method for preparing a corrosion-resistant polyionic liquid coating is further proposed.
[0061] S1: Cu@Cu(OH) 2 Preparation of
[0062] S2: preparing a polyionic liquid (PIL), wherein the preparation of the polyionic liquid (PIL) includes synthesizing 3-ethyl-1-vinylimidazolium bromide and preparing the PIL;
[0063] S3: Cu@Cu(OH) based on S1 and S2 2 - Preparation of PILs.
[0064] S1 includes at least the following steps:
[0065] Cut the 200-mesh copper mesh into 2 cm*2 cm and ultrasonically clean it in anhydrous ethanol and water for 10 minutes respectively;
[0066] The cleaned copper mesh was immersed in 10 mL of HCl solution (0.1 mol / L) for 10 min to remove organic pollutants and the oxidation layer;
[0067] The copper mesh soaked in hydrochloric acid was then washed three times with a large amount of water and then immersed in a solution containing NaOH (2.5 mol / L) and (NH 4 ) 2 S 2 O 8 (0.1 mol / L) in 50 mL of a mixed alkaline solution for 10 min, and then washed with distilled water;
[0068] Then it was placed on a watch glass and dried at 50°C under vacuum for 2 hours to obtain Cu@Cu(OH) 2 .
[0069] The synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 comprises at least the following steps:
[0070] Weigh 4.70 g (0.05 mol) of 1-vinylimidazole and 5.99 g (0.055 mol) of ethyl bromide into a flask, and stir at room temperature for 3 days;
[0071] The synthesized 3-ethyl-1-vinylimidazolium bromide (IL-Br) was washed with ethyl acetate and ether for several times, and then dried in vacuum at room temperature for 12 h to obtain 3-ethyl-1-vinylimidazolium bromide.
[0072] The NMR of 3-ethyl-1-vinylimidazolium bromide is as follows Figure 1 .
[0073] In the figure: 1 HNMR (400 MHz, DMSO-d 6 )δ(ppm):9.73(s,1H,N-CH=N + ),8.28(t,1H,one proton of CH=CH in ring),8.02(t,1H,one proton of CH=CH in ring),7.36(dd,J=15.6,8.8Hz,1H,one proton of CH 2 =),6.03(dd,J=15.6,2.4Hz,1H,one proton of CH 2 =),5.43(dd,J=8.8,2.4Hz,1H,=CH-),4.27(q,J=3.33Hz,2H,N + -CH 2 -),1.47(t,J=7.2Hz,3H,-CH 3 ).
[0074] 9.73 (s, 1H, N-CH=N+): A single peak signal, attributed to a proton in the imine structure.
[0075] 8.28 (t, 1H of CH=CH in the ring): triplet, attributed to a proton in the cyclic conjugated system.
[0076] 8.02 (t, 1H of CH=CH in the ring): triplet, attributed to a proton in the cyclic conjugated system.
[0077] 7.36 (dd, J = 15.6, 8.8 Hz, 1H, CH 2 =): Double doublet signal, attributed to a proton on the terminal double bond.
[0078] 6.03 (dd, J = 15.6, 2.4 Hz, 1H, CH 2 =): belongs to the other proton on the terminal double bond.
[0079] 5.43 (dd, J=8.8, 2.4 Hz, 1H, =CH-): attributed to a proton on a double-bonded carbon.
[0080] 4.27 (q, J = 3.33 Hz, 2H, N + -CH 2 -): A quartet of signals, which are attributed to two protons on a methylene group directly connected to a nitrogen atom and a methyl group.
[0081] 1.47(t,J=7.2Hz,3H,-CH 3 ): Triplet signal, attributed to the three protons on the methyl group directly connected to a methylene group.
[0082] These NMR data showed that the compound had a conjugated system, an olefinic double bond, and ethyl functional groups.
[0083] The preparation of the PIL in S2 comprises at least the following steps:
[0084] 3-ethyl-1-vinylimidazolium bromide monomer and azobisisobutyronitrile (AIBN) as a free radical initiator were dissolved in twice the weight of methanol at a ratio of 50:1 (molar ratio), stored under a nitrogen atmosphere, and reacted at 65°C for 6 hours;
[0085] The prepared PIL was washed with methanol to remove unreacted monomers, then extracted with cold acetone and centrifuged, and finally dried in a vacuum drying oven at 40° C. for 8 h to obtain the prepared PIL, which is a polyionic liquid.
[0086] The FTIR spectra of the prepared IL-Br monomer and PIL are shown in Figure 2. Figure 2 As shown, at 3180-2850cm -1 The broad band in the range is attributed to the stretching vibration of the CH group at 1632 cm -1 、1547cm -1 and 1160cm -1 The peak at 1663 cm on IL-Br is attributed to the characteristic band of imidazole ring, indicating the presence of imidazole groups in the polycation framework. -1 The peak at is caused by the unsaturated C=C stretching vibration of the vinyl group, but it is not observed in PIL, indicating that the vinyl group in IL-Br is consumed during the polymerization process and the obtained PIL has a higher degree of polymerization.
[0087] S3 includes at least the following steps:
[0088] Weigh PIL and methanol in a mass ratio of 1:2, dissolve PIL, and then prepare Cu@Cu(OH) 2 Soak in PIL methanol solution for 30 min;
[0089] Then, it was immersed in methanol for 1 h to wash away the excess polyionic liquid on the surface, and finally dried in vacuum at 60 °C for 2 h to obtain Cu@Cu(OH)2 -PIL.
[0090] Embodiment three:
[0091] A corrosion-resistant polyionic liquid coating, based on the above embodiment 1, a corrosion-resistant polyionic liquid coating is prepared by a preparation method of a corrosion-resistant polyionic liquid coating, namely Cu@Cu(OH) 2 -PIL.
[0092] Based on the above-mentioned Embodiment 1 and Embodiment 2, the following detection method is further proposed:
[0093] Oil-water separation experiment
[0094] The prepared Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL is fixed between two glass tubes. 20 ml of layered oil-water mixture or hexadecane / methanol mixture (w / w=1:1) is slowly poured into the upper tube, and the separation is quickly completed under the action of gravity, and the permeate is collected. When performing oil / water or hexadecane / methanol separation, the copper mesh is fully soaked with water or methanol, and then the mixture is flowed into the upper tube through a separatory funnel for oil / water or hexadecane / methanol separation. In addition, in order to visualize the separation experimentally, water and methanol are colored with methylene blue. The separation efficiency (η) is calculated by the following formula, η=M / M 0 *100%, where M 0 and M represent the mass of water or methanol before and after separation, respectively. The separation flux (F) is calculated by the following formula: F = V / At, where V is the separation volume and A is the effective filter copper mesh area (m 2 ), t is the separation time (h).
[0095] Stability test in harsh environment (acid, alkali, salt)
[0096] The prepared Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL was immersed in 50mL aqueous solution of 1mol / LHCl, 1mol / LNaOH and 1mol / LNaCl for 12h, washed with dedistilled water, dried in a vacuum oven at 60℃ for 2h, and used in oil-water separation experiment to investigate its stability under harsh environment.
[0097] Then the results and discussions are presented:
[0098] X-ray diffraction (XRD) analysis
[0099] The XRD pattern of the sample is as follows Figure 3 As shown. Figure 3(A) It can be seen that the pure copper mesh has obvious diffraction peaks at 2θ=43.7°, 50.8° and 74.5°, which correspond to the (111), (200) and (220) crystal planes of copper, respectively. Cu@Cu(OH) 2 and Cu@Cu(OH) 2 In addition to the obvious Cu diffraction peak, there are also diffraction peaks at 2θ=17.2°, 24.2°, 34.5°, 40.2° and 53.8° in -PIL, corresponding to Cu(OH) 2 The (020), (021), (002), (130) and (150) crystal planes of Cu(OH) 2 Successfully constructed on copper mesh. Figure 3 (B) Cu@Cu(OH) after treatment with HCl, NaOH and NaCl 2 From the XRD diagram, we can see that Cu@Cu(OH) 2 Cu@Cu(OH) after treatment with NaOH and NaCl 2 [NaOH] and Cu@Cu(OH) 2 The XRD pattern of [NaCl] did not change significantly, but the Cu@Cu(OH) treated with HCl 2 [HCl] produced new diffraction peaks at 2θ = 28.7°, 47.7°, and 56.5°, corresponding to the (111), (220), and (311) crystal planes of CuCl, respectively. Based on the XRD results, the proposed chemical reaction is as follows:
[0100] Cu(OH) 2 +Cu + 2HCl → 2CuCl + 2H 2 O
[0101] Obviously, Cu@Cu(OH) 2 It is easily corroded in an acidic environment. Figure 3 (C) Cu@Cu(OH) after treatment with NaOH and NaCl 2 -PIL[NaOH] and Cu@Cu(OH) 2 -PIL[NaCl] XRD patterns and Cu@Cu(OH) 2 -PIL, there is no obvious change, but the Cu@Cu(OH) 2 -Cu(OH) in PIL[HCl] 2 The diffraction peaks were significantly weakened or even disappeared, but no CuCl diffraction peaks appeared, indicating that the presence of PIL can play a certain protective role on the filter material surface under strong acid conditions.
[0102] Scanning electron microscopy (SEM) analysis
[0103] Figure 4 The SEM images show that the original copper mesh has a smooth surface, while the Cu@Cu(OH) 2 The surface is completely covered by a dense array of nanoneedles ( Figure 4 b), the XRD results show that needle-shaped copper hydroxide is generated on the surface of copper after being corroded by ammonia. This nanoneedle array can increase the roughness of the filter material surface, enhance the wettability of the filter material, and improve the separation efficiency. Figure 4 c can be found Cu@Cu(OH) 2 - There are irregular flakes on the surface of PIL, which may be caused by the uneven coating of PIL on the filter surface, which also shows that Cu@Cu(OH) 2 -PIL The surface of the filter medium is covered with PIL. Figure 4 de is Cu@Cu(OH) 2 SEM images after immersion in HCl, NaOH, and NaCl. Figure 4 d shows that Cu@Cu(OH) 2 The needle-shaped copper hydroxide on the surface completely disappeared, and a smooth surface appeared again. Combined with the XRD results, it can be seen that after HCl treatment, HCl and Cu(OH) 2 and metallic Cu to form CuCl. Figure 4 e and 4f show that the Cu@Cu(OH) 2 The needle-shaped copper hydroxide layer in the middle shows serious structural collapse. 2 The structure is unstable in harsh environments such as strong acid, strong alkali, and strong salt. Figure 4 gi is Cu@Cu(OH) 2 -SEM images of PIL after treatment with HCl, NaOH and NaCl, Figure 4 g shows that after HCl treatment, many nanosheet structures are accumulated on the surface of the copper mesh, which is different from the smooth surface of 4d, indicating that the surface-coated PIL can effectively protect the surface structure of the filter material under strong acid. Figure 4 h and 4i results show that the Cu@Cu(OH) 2 -The needle-shaped copper hydroxide layer is still intact on the surface of PIL, which further illustrates that the coating of PIL makes the filter material very stable in harsh environments such as strong acid, strong alkali, and strong salt.
[0104] XPS analysis
[0105] XPS characterization of Cu@Cu(OH) 2 、Cu@Cu(OH) 2-PIL filter materials, and their chemical compositions after treatment with HCl, NaOH and NaCl. The full spectrum is as follows Figure 5 A and 5B. Figure 5 Cu@Cu(OH) in A 2 、Cu@Cu(OH) 2 [HCl], Cu@Cu(OH) 2 [NaOH] and Cu@Cu(OH) 2 Compared with [NaCl] Figure 5 Cu@Cu(OH) in B 2 -PIL, Cu@Cu(OH) 2 -PIL[HCl],Cu@Cu(OH) 2 -PIL[NaOH] and Cu@Cu(OH) 2 -PIL[NaCl] showed N element, which was attributed to the N element contained in the introduced PIL. The results verified that PIL was successfully introduced into Cu@Cu(OH) 2 In addition, Cu@Cu(OH) 2 -Br element can be detected in PIL, which is also attributed to the Br in PIL - , but Cu@Cu(OH) 2 -PIL[HCl],Cu@Cu(OH) 2 -PIL[NaOH] and Cu@Cu(OH) 2 -No Br element was detected in PIL[NaCl], which may be due to the exchange of anions in PIL during the immersion of the filter material in HCl, NaOH and NaCl solutions.
[0106] Figure 5 (C) is the Cu 2p spectrum of the filter material. 3 / 2 and Cu2p 1 / 2 Composition. Among them, Cu@Cu(OH) 2 、Cu@Cu(OH) 2 [NaOH] and Cu@Cu(OH) 2 Cu 2p of [NaCl] 3 / 2 There is only one sharp characteristic peak at 935.0±0.3 eV, corresponding to Cu 2+ , and Cu appeared at 938.2-946.7eV 2+ The satellite characteristic peaks are due to Cu(OH) 2 It is worth noting that Cu@Cu(OH) 2 Cu in [HCl] 2+ The characteristic peak and its satellite peaks disappeared, and Cu appeared at 933.2eV. 0or Cu + Characteristic peaks, indicating Cu@Cu(OH) 2 After HCl treatment, Cu(OH) 2 It reacts with HCl to form Cu 0 or Cu + , XRD results have confirmed the existence of CuCl. Figure 5 (D) Cu@Cu(OH) 2 、Cu@Cu(OH) 2 [NaOH] and Cu@Cu(OH) 2 The peak of [NaCl] at 531.0±0.3 eV corresponds to the peak of the crystalline oxidation state, combined with Figure 5 (C) The results show that Cu(OH) 2 The presence of Cu@Cu(OH) 2 In [HCl], 532.3 eV is H 2 O peak, which may be Cu(OH) on the filter surface 2 The H generated by the reaction with HCl 2 O.
[0107] Figure 5 (E) Cu 2p spectrum, Cu@Cu(OH) 2 -PIL, Cu@Cu(OH) 2 -PIL[HCl],Cu@Cu(OH) 2 -PIL[NaOH] and Cu@Cu(OH) 2 -PIL[NaCl] detected Cu at 934.7±0.2eV 2+ The characteristic peak of Cu appeared at 938-945eV 2+ Satellite peaks, combined Figure 5 The O1s spectrum of (F) shows that there is Cu(OH) on the surface of these filter materials. 2 In addition, Cu@Cu(OH) 2 -PIL[HCl] also showed Cu at 933.1eV 0 / Cu + Characteristic peak, this is still Cu(OH) 2 The result of the reaction with HCl. Figure 5 (C)Cu@Cu(OH) 2 [HCl] only Cu 0 / Cu + Different, Cu@Cu(OH) 2 -PIL[HCl] contains both Cu 0 / Cu + , and there is also Cu 2+ , indicating that Cu@Cu(OH)2 The surface-coated PIL can protect the chemical composition of the filter surface to a certain extent in a strong acid environment. Figure 5 The results of (C) to (D) confirm that Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -Cu(OH) still exists on the surface of PIL after NaOH and NaCl treatment 2 , indicating that Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL can show excellent chemical stability in strong alkaline and strong salt environments.
[0108] Surface wettability of filter media
[0109] The surface wettability of the filter material was studied by measuring the contact angle of a water droplet. Figure 6 As shown in Figure 2, the original copper mesh exhibits hydrophobicity, and the water contact angle in air is 109.9°. 2 and Cu@Cu(OH) 2 -PIL was diffused and absorbed immediately after contact, and the angle of water was 0°, indicating that Cu@Cu(OH) 2 The surface is super hydrophilic. The water droplets and Cu@Cu(OH) 2 -PIL, the initial contact angle was 55.4°, but the water droplet could diffuse and penetrate into the filter material within 5 seconds, making the water contact angle finally 0°, indicating that Cu@Cu(OH) 2 -PIL surface is also hydrophilic. 2 In comparison, Cu@Cu(OH) 2 The initial contact angle of -PIL to water becomes larger, and the reason may be that the alkyl group of the imidazolium substituent in the polyionic liquid reduces the surface tension of the polyionic liquid, thereby weakening the hydrophilicity of the filter surface when it contacts water.
[0110] Oil-water separation experiment
[0111] Low viscosity oil (n-hexane and petroleum ether) and high viscosity oil (n-hexadecane) were selected as the oil phase and the Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL's "water removal" performance. Hexadecane was selected as the oil phase and the Cu@Cu(OH) 2 and Cu@Cu(OH) 2-PIL's "methanol removal" performance. All experiments were conducted with gravity as the only driving force, with water or methanol completely permeating through the filter material and the oil phase being blocked and staying on the top of the filter material. For different oil-water mixtures, the oil can be blocked at the top of the filter material for at least 2 hours. Figure 7 As shown in (A), Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL has a separation efficiency of 93%-97%, and the separation efficiency for oil-water mixtures of high-viscosity oils is higher than that for oil-water mixtures of low-viscosity oils. Since the copper mesh is larger, the separation process is faster. The entire oil / water separation is completed in only 3-5 seconds after the three filter materials are stacked. Therefore, the filter material has a higher permeability. Cu@Cu(OH) 2 In a low viscosity oil (n-hexane and petroleum ether) water mixture, the water flux value under gravity is about 40,000 L / (m 2 h) (shown in Figure 7(B)), for a high viscosity oil (n-hexadecane) water mixture, the water flux value under gravity is about 30,000 L / (m 2 ·h). Cu@Cu(OH) 2 -PIL in petroleum ether / water (higher than 50,000L / (m 2 ·h)) and n-hexadecane / water (higher than 40,000 L / (m 2 The water flux in the mixture h) is significantly higher than that in Cu@Cu(OH) 2 At the same time, n-hexadecane and methanol were used as two solvents with different polarities to test the Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL separation performance for organic solvents of different polarities. First, methanol will quickly pass through the oil-wetted Cu@Cu(OH) 2 , after methanol flows out, Cu@Cu(OH) 2 Cannot hold n-hexadecane, then slowly passes through Cu@Cu(OH) 2 In contrast, Cu@Cu(OH) 2 When PIL is used to separate methanol and n-hexadecane, after methanol flows out, n-hexadecane will be temporarily closed and then slowly flow down. Its methanol separation efficiency is 90.3±1.8%, and the methanol flux value under gravity is about 19,000L / (m 2 ·h), the results show that Cu@Cu(OH) 2 -PIL has a certain separation ability for methanol and n-hexadecane.
[0112] Considering that industrial wastewater is mostly acidic, alkaline or saline, this work investigated the Cu@Cu(OH) 2and Cu@Cu(OH) 2 -PIL corrosion resistance in harsh environments. Using n-hexane as the oil phase, the Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL is immersed in 1mol / LHCl, 1mol / LNaOH and 1mol / LNaCl aqueous solution for 12h to measure the oil / water separation performance of the filter material. Three pieces of the immersed filter material are stacked and then separated into oil / water. The entire separation process is completed within 3-5 seconds. The separation efficiency is as follows Figure 8 As shown in (A), Cu@Cu(OH) 2 When the n-hexane / water separation was performed after HCl soaking, the filter material could not retain the n-hexane after the water flowed out, resulting in separation failure. 2 After soaking in NaOH and NaCl, the separation efficiency of n-hexane / water mixture was greater than 93%, and the water flux was greater than 40,000 L / (m 2 ·h). Therefore, after soaking in NaOH and NaCl, Cu@Cu(OH) 2 Still has good oil / water separation performance. 2 Different, Cu@Cu(OH) 2 -PIL can be used for separation of n-hexane / water mixture after being soaked in HCl, NaOH and NaCl, with separation efficiencies of 90.0%, 94.7% and 92.8%, respectively. 2 -PIL water flux value is less than 40,000L / m 2 h, while Cu@Cu(OH) 2 -PIL water flux value is still above 40,000L / (m 2 ·h). This indicates that HCl immersion will lead to Cu@Cu(OH) 2 -PIL oil separation efficiency decreased, while NaOH and NaCl immersion could enhance the Cu@Cu(OH) 2 -PIL still has good oil / water separation performance.
[0113] The above results show that Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PILs have good alkali and salt resistance, but Cu@Cu(OH) 2 Not acid-resistant, while Cu@Cu(OH) 2 -PIL has a certain acid resistance. This is consistent with the Cu@Cu(OH) 2 and Cu@Cu(OH) 2-PIL surface structure and chemical properties. XRD, SEM and XPS results of the filter material show that after NaOH and NaCl immersion, Cu@Cu(OH) 2 -PIL surface still retains the needle-shaped copper hydroxide layer intact, while the Cu@Cu(OH) 2 Although the needle-shaped copper hydroxide layer showed serious structural collapse, its surface chemical composition did not change, which may be due to the Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL still has good oil / water separation performance. In addition, SEM results show that after HCl immersion, Cu@Cu(OH) 2 Severe acid corrosion caused the needle-shaped copper hydroxide on the surface to disappear completely, while Cu@Cu(OH) 2 -PIL surface is deposited with nanosheet structures. XRD and XPS further confirmed that after HCl treatment, Cu@Cu(OH) 2 Surface Cu(OH) 2 Completely react with HCl to generate metallic Cu or CuCl, while Cu@Cu(OH) 2 -PIL except Cu 0 / Cu + , and Cu(OH) 2 Therefore, in a strong acid environment, Cu@Cu(OH) 2 The surface-coated PIL protects the stability of the surface structure and chemical composition of the filter material to a certain extent, making Cu@Cu(OH) 2 -PIL has certain oil-water separation performance. The above results show that Cu@Cu(OH) 2 -PIL has the ability to be used in wastewater environments.
[0114] In summary:
[0115] In the present invention, a super-hydrophilic Cu@Cu(OH) 2 The PIL-modified Cu@Cu(OH) filter material was successfully prepared for oil-water separation in wastewater environment. 2 -PIL. The separation results of laminar oil-water mixtures show that Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL can effectively separate oil / water mixtures, and Cu@Cu(OH) 2-PIL also has a certain separation ability of organic solvents with different polarities. XRD, SEM and XPS results show that Cu@Cu(OH)2+ after immersion in NaOH and NaCl 2 The surface copper hydroxide layer structure collapsed, but the surface chemical composition did not change. Cu@Cu(OH) 2 -PIL surface still retains a complete nano-copper hydroxide layer. Therefore, Cu@Cu(OH) 2 and Cu@Cu(OH) 2 -PIL still has good oil / water separation performance. However, the difference is that the Cu@Cu(OH) 2 The surface becomes smooth due to severe acid corrosion, while Cu@Cu(OH) 2 -PIL after HCl immersion has a nanosheet-like structure on its surface. 0 / Cu + In addition to the species, there are also some Cu(OH) 2 , making Cu@Cu(OH) 2 -PIL also has certain oil-water separation performance in acidic environment. The above results show that polyionic liquid as a coating successfully protects the filter material from (or reduces) the corrosion and side effects of acid, alkali and salt in the wastewater environment, and improves the separation performance and stability of the filter material in harsh environment.
[0116] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a corrosion-resistant polyionic liquid coating, characterized in that: At least the following steps are included: S1: After cleaning the copper mesh, the mesh is treated with HCl solution and then immersed in HCl solution, and then immersed in a mixed alkaline solution to complete the preparation of Cu@Cu(OH)2; S2: preparing a polyionic liquid, wherein the preparation of the polyionic liquid includes synthesizing 3-ethyl-1-vinyl imidazolium bromide and preparing a PIL; S3: Preparation of Cu@Cu(OH)2-PIL based on S1 and S2.
2. The method for preparing a corrosion-resistant polyionic liquid coating according to claim 1, characterized in that: The S1 at least comprises the following steps: Cut a 180-220 mesh copper mesh into a square with a size of 1-3 cm*1-3 cm, and ultrasonically clean it in anhydrous ethanol and water for 8 min to 16 min respectively; Soak the cleaned copper mesh in 6 mL to 18 mL of HCl solution for 8 min to 16 min to remove organic pollutants and oxidation layer; Subsequently, the copper mesh soaked in hydrochloric acid is washed with a large amount of water for 3 to 5 times, and the washed copper mesh is soaked in 40 mL to 80 mL of a mixed alkaline solution containing NaOH and (NH4)2S2O8 to react for 5 min to 15 min, and then washed with distilled water, wherein the concentration of the NaOH used is 2 to 3 mol / L, and the concentration of the (NH4)2S2O8 used is 0.1 to 0.2 mol / L; Then it was placed on a watch glass and baked at 45°C to 65°C under vacuum conditions for 1.5h to 3h to obtain Cu@Cu(OH)2.
3. The method for preparing a corrosion-resistant polyionic liquid coating according to claim 2, characterized in that: The synthesis of 3-ethyl-1-vinyl imidazole bromide in S2 at least comprises the following steps: Weigh 4.5 g to 5.0 g of 1-vinylimidazole and 5.0 g to 6.0 g of ethyl bromide in a flask, and stir at a certain temperature for 48 h to 96 h, wherein the temperature includes 15 ° C to 25 ° C; The synthesized 3-ethyl-1-vinylimidazolium bromide is washed with ethyl acetate and ether for multiple times, and then dried in vacuum at room temperature for 8h to 14h to obtain 3-ethyl-1-vinylimidazolium bromide, which is IL-Br.
4. The method for preparing a corrosion-resistant polyionic liquid coating according to claim 3, characterized in that: The preparation of the PIL in S2 at least comprises the following steps: Dissolve 3-ethyl-1-vinyl imidazolium bromide monomer and azobisisobutyronitrile as a free radical initiator in twice the weight of methanol at a ratio of 49 to 52:1, store under nitrogen atmosphere, and react at 55°C to 70°C for 4h to 8h; The prepared PIL is washed with methanol to remove unreacted monomers, then extracted with cold acetone and centrifuged, and finally dried in a vacuum drying oven at 40° C. to 60° C. for 7 h to 8 h to obtain the prepared PIL, which is a polyionic liquid.
5. The method for preparing a corrosion-resistant polyionic liquid coating according to claim 4, characterized in that: The S3 at least includes the following steps: Weigh PIL and methanol in a mass ratio of 1:2, dissolve PIL, and then soak the prepared Cu@Cu(OH)2 in the PIL methanol solution for 20 min to 30 min; Then, the surface of the composite was immersed in methanol for 0.5 h to 1 h to wash away the excess polyionic liquid, and finally, the composite was vacuum dried at 50° C. to 70° C. for 2 h to 3 h to obtain Cu@Cu(OH)2-PIL.
6. A corrosion-resistant ionic liquid coating, characterized in that: The corrosion-resistant polyionic liquid coating is prepared by the method for preparing a corrosion-resistant polyionic liquid coating as described in any one of claims 1 to 5, namely Cu@Cu(OH)2-PIL.
Citation Information
Patent Citations
Preparation method of solid-phase microextraction fibers by bonding metal wire with polyion liquid
CN102600816A
Imidazole unsaturated ionic liquid and preparation method thereof
CN104529901A
(1-vinyl-3-ethyl imidazole borate) polyion liquid / polyvinyl alcohol polymer composite material and preparation method thereof
CN105482327A
Preparation method of copper grid composite ionic liquid gel flexible transparent electrode
CN109817381A
Polyion liquid and metal organic framework composite material and application thereof in removal of < 99 > Tc nuclide
CN115197435A